Histone deacetylase 1 (HDAC1): A key player of T cell-mediated arthritis. Issue 108 (March 2020) - Göschl, Lisa; Preglej, Teresa; Boucheron, Nicole; Saferding, Victoria; Müller, Lena; Platzer, Alexander; Hirahara, Kiyoshi; Shih, Han-Yu; Backlund, Johan; Matthias, Patrick; Niederreiter, Birgit; Hladik, Anastasiya; et al.
Abstract: Rheumatoid Arthritis (RA) represents a chronic T cell-mediated inflammatory autoimmune disease. Studies have shown that epigenetic mechanisms contribute to the pathogenesis of RA. Histone deacetylases (HDACs) represent one important group of epigenetic regulators. However, the role of individual HDAC members for the pathogenesis of arthritis is still unknown. In this study we demonstrate that mice with a T cell-specific deletion of HDAC1 ( HDAC1-cKO ) are resistant to the development of Collagen-induced arthritis (CIA), whereas the antibody response to collagen type II was undisturbed, indicating an unaltered T cell-mediated B cell activation. The inflammatory cytokines IL-17 and IL-6 were significantly decreased in sera of HDAC1-cKO mice. IL-6 treated HDAC1-deficient CD4 + T cells showed an impaired upregulation of CCR6. Selective inhibition of class I HDACs with the HDAC inhibitor MS-275 under Th17-skewing conditions inhibited the upregulation of chemokine receptor 6 (CCR6) in mouse and human CD4 + T cells. Accordingly, analysis of human RNA-sequencing (RNA-seq) data and histological analysis of synovial tissue samples from human RA patients revealed the existence of CD4 + CCR6 + cells with enhanced HDAC1 expression. Our data indicate a key role for HDAC1 for the pathogenesis of CIA and suggest that HDAC1 and other class I HDACs might be promising targets of selective HDAC inhibitors (HDACi) for the treatment of RA. Highlights: HDAC1 deficiency in T cells protects from the development of Collagen-induced arthritis (CIA). Diminished expression of Th17 associated cytokines in the serum of HDAC1-cKO mice after CIA induction. Disturbed regulation of CCR6 in HDAC1 deficient T cells upon IL-6 stimulation. Selective HDAC inhibition reduces CCR6 expression in human and murine Th17 cells.